Phospholipid Scramblases: Role in Cancer Progression and Anticancer Therapeutics - Behuria, Himadri Gourav; Dash, Sabyasachi; Sahu, Santosh Kumar (Frontiers in Genetics, 2022)
Phospholipid scramblases (PLSCRs) that catalyze rapid mixing of plasma membrane lipids result in surface exposure of phosphatidyl serine (PS), a lipid normally residing to the inner plasma membrane leaflet. PS exposure provides a chemotactic eat-me signal for phagocytes resulting in non-inflammatory clearance of apoptotic cells by efferocytosis. However, metastatic tumor cells escape efferocytosis through alteration of tumor microenvironment and apoptotic signaling. Tumor cells exhibit altered membrane features, high constitutive PS exposure, low drug permeability and increased multidrug resistance through clonal evolution. PLSCRs are transcriptionally up-regulated in tumor cells leading to plasma membrane remodeling and aberrant PS exposure on cell surface. In addition, PLSCRs interact with multiple cellular components to modulate cancer progression and survival. While PLSCRs and PS exposed on tumor cells are novel drug targets, many exogenous molecules that catalyze lipid scrambling on tumor plasma membrane are potent anticancer therapeutic molecules. In this review, we provide a comprehensive analysis of scramblase mediated signaling events, membrane alteration specific to tumor development and possible therapeutic implications of scramblases and PS exposure.